Orthoptera Tettigoniidae (Conocephalinae, Hexacentrinae, Phaneropterinae, Mecopodinae, Hetrodinae) from some protected areas of Central African Republic - Massa, Bruno; Annoyer, Philippe; Perez, Cyrille; Danflous, Samuel; Duvot, Guilhem (Zootaxa, 2020)
This paper is a contribution to the distribution, taxonomy and phenology of Orthoptera Tettigoniidae of Central African Republic. Thanks to scientific expeditions and entomological missions, 2155 Orthoptera belonging to 118 species of five subfamilies of Tettigoniidae have currently been studied. Examined material is here listed with its known distribution. New genera and species have been found and here described: Eurycoplangiodes sanghaensis Massa, n. gen. and n. sp. Paraeulioptera emitflesti Massa, n. gen. and n. sp., Paraeurycorypha Massa, n. gen. ocellata Massa et Annoyer, n. sp., Arantia (Arantia) gretae Massa, n. sp., Arantia (Euarantia) syssamagalei Massa et Annoyer, n. sp. and Dapanera brevistylata Massa, n. sp. Overall, from 2012 to 2020, the study of the orthopteran material collected in the scientific expeditions to Central Africa carried out since 1984, enabled the description of 6 new genera and 27 new species. They represent 22.8% of the total amount of species currently recorded in the protected areas where this scientific activity has been carried out. This demonstrates that these areas still hold a high number of new species, representing a biodiversity hotspot.